2021
DOI: 10.3390/ijms23010293
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNAs miR-25-3p, miR-185-5p and miR-132-3p in Late Onset Fetal Growth Restriction, Validation of Results and Study of the Biochemical Pathways Involved

Abstract: In a prospective study, 48 fetuses were evaluated with Doppler ultrasound after 34 weeks and classified, according to the cerebroplacental ratio (CPR) and estimated fetal weight (EFW), into fetuses with normal growth and fetuses with late-onset fetal growth restriction (LO-FGR). Overexpression of miRNAs from neonatal cord blood belonging to LO-FGR fetuses, was validated by real-time PCR. In addition, functional characterization of overexpressed miRNAs was performed by analyzing overrepresented pathways, gene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 91 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…The miRNAs showing significantly different expression in exosomes were all up-regulated ( Table 3 ) and the majority of them have already been described in connection with various pregnancy-related disorders. These included hsa-miR-1-3p ( 81 ), hsa-miR-183-5p ( 82 , 83 ), hsa-miR-185-5p ( 84 ), hsa-miR-186-5p ( 85 ), and hsa-miR-20a-5p ( 81 ), and the latter three are also normally expressed at higher levels in the first trimester of healthy pregnancies ( 86 ), although in certain studies where exosomes were not separated they are referred to as plasma-specific miRNAs ( 87 ). Interestingly, hsa-miR-26b-5p showed a tendency for upregulation in PE, but was not found to be differentially expressed in another study ( 88 ), which may be due to the heterogeneous patient population included in that study.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs showing significantly different expression in exosomes were all up-regulated ( Table 3 ) and the majority of them have already been described in connection with various pregnancy-related disorders. These included hsa-miR-1-3p ( 81 ), hsa-miR-183-5p ( 82 , 83 ), hsa-miR-185-5p ( 84 ), hsa-miR-186-5p ( 85 ), and hsa-miR-20a-5p ( 81 ), and the latter three are also normally expressed at higher levels in the first trimester of healthy pregnancies ( 86 ), although in certain studies where exosomes were not separated they are referred to as plasma-specific miRNAs ( 87 ). Interestingly, hsa-miR-26b-5p showed a tendency for upregulation in PE, but was not found to be differentially expressed in another study ( 88 ), which may be due to the heterogeneous patient population included in that study.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is considered to maintain the calcium homeostasis in the myometrium and contribute to avoiding preterm birth. On the other hand, miR-25b-3p is suggested for adverse pregnancy outcomes including hypertensive disorders, fetal growth restriction, and preterm birth [ 17 , 35 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs are one of the small noncoding RNAs that can regulate gene expression by targeting messenger RNAs [ 4 ]. It is suggested that miRNAs in maternal circulation influence the state of metabolism during pregnancy, and the variation of miRNAs is beneficial for finding pregnancy disorders such as preeclampsia and fetal intrauterine growth retardation [ 17 , 18 ]. In addition, miRNAs have a possibility to influence delivery processes [ 21 , 36 ] presented the existence of placenta-derived miRNAs and the possibility of miRNAs in the signaling from the fetal membrane to the uterus, especially in the mechanism of birth induction.…”
mentioning
confidence: 99%
“…Another possible target, in this case for the 3′ end of miRNA-25, found with regards to vascular dysfunction is angiogenic factor 1, which is related to correct blood vessel development [ 25 ].…”
Section: Discussionmentioning
confidence: 99%